Translation Ethics: From Invisibility to Difference - Cruz, Xénon (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2017)
Since its inception as an academic discipline, Translation Studies has contributed in the past few decades to raise the status of translation as a field of critical thought in general, and of translators as cultural agents in particular. However, translation and translators have been around for millennia, and to speak of them is to speak of the very roots of language and civilization. It is also to speak about ethics. In this article, I propose to briefly review the history of translation ethics, by beginning to make an etymological and conceptual distinction between ethics and morality, and then focusing on the notion of fidelity as the traditional moral guideline for translators. Afterwards, I will try to demonstrate the paradigm shift that has, more recently, been taking place in translation discourses. Casting away the age-old veil of neutrality and invisibility which has covered translation practice in the past, many thinkers have come to reimagine and reposition what it means to translate and, more important, what it means to translate ethically.